Features of dense plasma formation in the reflex discharge on gas-metal mixes - Kovtun, Yu.V. (Вопросы атомной науки и техники, 2013)
The paper briefly summarizes the data from studies of multicomponent gas-metal plasma in a pulsed reflex discharge. The processes of injection of sputtered-and-ionized working materials (Ti, Mo, W, U) into the reflex discharge plasma have been considered in the framework of the steady-state model. The measured data on the rotational velocity of the gas-metal multicomponent plasma formed in the reflex discharge correlate with the critical ionization velocity (CIV) values.